PYTHON-BASED STATISTICAL ANALYSIS OF THE ECOLOGICAL VARIABLES IN THE ITALIAN ALPS - LEMENKOVA, Polina (Journal of process management and new technologies, 2025)
The high Alpine region of northern Italy is characterized by unique ecosystems, a complex hydrogeological setting, steep topographic gradients, variety of vegetation types and landscape patches, and varied in climatic and meteorological factors. Alpine ecosystem is even more complex when the vegetation composition is dominated by coniferous trees, since underground flow conditions and directions have unpredictable water quantities. Modelling such ecosystems requires advanced tools of programming and computing approaches, such as Python. This article is focused on the distributed water balance modelling in alpine catchments. The area is dominated by the coniferous forests (spruce, pine) with trees of different age (old >200 years and young,
Keywords: Python; modelling; environmental monitoring; climate; statistics; data analysis